2021
DOI: 10.3389/fphar.2021.648861
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Huang-Lian Jie-Du Decoction on Glucose and Lipid Metabolism in Type 2 Diabetes Mellitus: A Systematic Review and Meta-Analysis

Abstract: Background: Type 2 diabetes mellitus (T2DM) is a heterogeneous disease characterized by persistent hyperglycemia. Huang-Lian Jie-Du decoction (HLJDD) is a traditional Chinese medicine formula which is widely used in treating T2DM in China. A thorough understanding of current body of evidence is needed.Objective: this study aims to summarize the clinical evidence of HLJDD for T2DM to provide an up-to-date and accurate understanding of this issue for research and clinical practice.Methods: Six databases were sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…For T2DM, the fasting blood glucose (FBG) level, two-hour postprandial glucose (2hPG) level, weight, and waist circumference (WC) were the main indicators ( Jiang et al, 2020 ; Hu et al, 2021 ). HbA1c represents the average blood glucose level in the preceding 3 months and was the main outcome indicator ( Altobelli et al, 2021 ; Kim and Hur, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…For T2DM, the fasting blood glucose (FBG) level, two-hour postprandial glucose (2hPG) level, weight, and waist circumference (WC) were the main indicators ( Jiang et al, 2020 ; Hu et al, 2021 ). HbA1c represents the average blood glucose level in the preceding 3 months and was the main outcome indicator ( Altobelli et al, 2021 ; Kim and Hur, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…After screening the titles and abstracts, 93 studies were retained. After screening the articles in full text, we further excluded 46 records, so a total of 47 studies [ 11 – 57 ] were reviewed ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The basic information of the included literature is listed in Table 1 ; 46 studies (97.9%) were from China [ 11 – 33 , 35 – 57 ], and 1 (2.1%) was from Canada [ 34 ]. According to different TCM therapies, they were divided into herbs or herbal extracts, compounds, powders, decoctions, pills, external treatment, basic theories and treatment principles of TCM, proprietary Chinese medicines, and unspecified TCM integrated therapies ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coptidis Rhizoma (Coptis chinensis Franch, CR) and Scutellariae Radix (Scutellaria baicalensis Georgi, SR) are classical TCM combinations in clinic, which originated from Treatise on Febrile Diseases (Shang Han Lun) in 219 AD. As the herb pair, CR-SR are used together to mutually reinforce e cacy, such as Huanglian jiedu decoction, Gegenqinlian decoction and Xiexin decoction and the like [18][19][20]. Currently, many studies have shown there were phytochemical self-assembly to form supramolecular in the process of co-decoction of CR-SR [21][22][23].…”
Section: Introductionmentioning
confidence: 99%